CARBON STORAGE IN FOREST AND COFFEE BASED LAND MANAGEMENT AT BATU TEGI - Arief Darmawan; Christine Wulandari; Indra Gumay Febryano; Hari Kaskoyo; Yulia Rahma Fitriana; Rahmat Safe’i; Susni Herwanti; Dian Iswandaru; Novriyanti; M. Pahlevi Fadhlurrazzaq Levi (Jurnal Belantara, 2026)
Climate change is a global issue that requires mitigation strategies in various sectors, including forestry. Agroforestry, which combines trees with agricultural crops, is considered a strategy that can reduce greenhouse gas emissions by increasing carbon storage. This study aims to estimate and analyze the amount of carbon stored in three different land cover types found in a landscape of forest management unit (FMU), namely agroforestry coffee, monoculture coffee, and forest. Carbon stock analysis was conducted using a non-destructive approach on 36 sample plots evenly distributed across the three land cover types. The results showed that the highest carbon stock was found in forested area, followed by agroforestry coffee and monoculture coffee. However, the agroforestry system showed a fairly high carbon storage potential and was close to forest land, especially due to the presence of species such as Swietenia macrophylla and Coffea canephora. These findings indicate that the agroforestry system has great potential in climate change mitigation strategies by increasing carbon stocks, making it worthy of being an alternative to support forest conservation and rehabilitation.